2020
DOI: 10.1097/sla.0000000000004146
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury After Esophageal Cancer Surgery

Abstract: Objective: To determine the incidence, risk factors, and consequences of AKI in patients undergoing surgery for esophageal cancer Summary of Background Data: Esophageal cancer surgery is an exemplar of major operative trauma, with well-defined risks of respiratory, cardiac, anastomotic, and septic complications. However, there is a paucity of literature regarding AKI. Methods: consecutive patients undergoing curative-intent surgery for esophageal cancer from 2011 to 2017 in 3 high-volume centers were studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 46 publications
0
18
1
Order By: Relevance
“…The underlying mechanism may be that EHS leads to severe injury in other organs, such as the brain, or DIC, which has a greater impact on 90-day mortality than AKI. These results are different from those associated with sepsis or surgery (29)(30)(31). But this result still needs a large sample study to be confirmed in the future.…”
Section: Mb: a Better Biomarker Of Rmmentioning
confidence: 56%
“…The underlying mechanism may be that EHS leads to severe injury in other organs, such as the brain, or DIC, which has a greater impact on 90-day mortality than AKI. These results are different from those associated with sepsis or surgery (29)(30)(31). But this result still needs a large sample study to be confirmed in the future.…”
Section: Mb: a Better Biomarker Of Rmmentioning
confidence: 56%
“…In total, our search identified 1260 records of which 113 records were removed as duplicates and a further 1091 records were excluded for not meeting our eligibility criteria upon the screening of the title and abstract. After a full-text examination, 18 studies met our selection criteria [5][6][7][8][9][10][11][12][27][28][29][30][31][32][33][34][35][36]. The reference lists for the bibliographies of the text articles were screened, which revealed two reports that met our inclusion criteria [19,37].…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 presents the clinical characteristics of all the included studies. Of the 20 studies analyzed, 15 were retrospective observational studies [5-7,9,19,27-31,33-37], 4 were prospective observational studies [8,11,12,32], and 1 was a retrospective nested casecontrol study [10]. Two studies documented mixed thoracic surgical populations [19,29], thirteen documented lung surgical populations [5,7,9,11,12,27,30,[32][33][34][35][36][37], and five were of esophageal surgical populations [6,8,10,28,31].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations